2021
DOI: 10.1155/2021/8884126
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Serum Cystatin C for Early Recognition of Nephropathy in Type 2 Diabetes Mellitus

Abstract: Objectives. Diabetic nephropathy is one of the major complications that develop over time in type 2 diabetes mellitus (T2DM). This prospective study was conducted to assess the diagnostic accuracy of serum cystatin C in detecting diabetic nephropathy at earlier stages. Materials and Methods. This study was undertaken on 50 cases of T2DM and 50 healthy subjects as controls. Demographic and anthropometric data and blood and urine samples were collected. The concentration of serum cystatin C (index test) and trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
4
8
0
4
Order By: Relevance
“…The current study found positive relation between duration of diabetes and level of serum cystatin-c in diabetic patient group (p < 0.027). Other study illustrated positive relation between serum cystatin-c and age in T2DM patients [7].…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The current study found positive relation between duration of diabetes and level of serum cystatin-c in diabetic patient group (p < 0.027). Other study illustrated positive relation between serum cystatin-c and age in T2DM patients [7].…”
Section: Resultsmentioning
confidence: 84%
“…Serum creatinine was unable to detect early decline in GFR owing to the fact that levels of serum creatinine begins to rise above normal range only in case of kidney had lost approximately 50% of its function, suggesting any change in GFR can occur before serum creatinine tends to be abnormal. Other study con rmed that cystatin-C is a well-de ned marker which is advised to be assessed for early DN diagnosis and progression [7,28]. Previous study had mentioned that nutritional status, in ammatory processor and dietary factors had no impact on cystatin-c levels.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although serum creatinine is a traditional biomarker, it is not very accurate because its values do not boost up until the GFR is lowered to less than 50% of normal [ 29 ]. Cystatin C and β 2MG, as potential markers of renal injury, have higher accuracy in diagnosing DN than serum creatinine [ 30 , 31 ]. Meanwhile, they are also a classic biomarker of renal tubulointerstitial injury [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is found also in all biological fluids 5 . It is synthesized by all nucleated cells at a stable rate and different factors such as sex, protein ingestion, inflammation, or muscle mass had no impact on its concentration 6 . It represents an ideal marker of endogenous glomerular filtration rate.…”
Section: Introductionmentioning
confidence: 99%